Gynaecological laparoscopic surgery: eight years experience in the Yaoundé Gynaeco-Obstetric and Paediatric Hospital, Cameroon. (April 2014) - Mboudou, Emile; Morfaw, Frederick LI; Foumane, Pascal; Sama, Julius Dohbit; Mbatsogo, Bernard Armand Enama; Minkande, Jacqueline Ze
This is a retrospective analysis of eight years of gynaecological laparoscopic surgery in a resource-limited setting. All gynaecological patients managed by laparoscopy at the Yaoundé Gynaeco-Obstetric and Paediatric Hospital from 1 January 2004 to 30 November 2011 were included. Amongst the 9194 gynaecological surgeries performed during the study period, 6.9% (633) were done by laparoscopy. Most of the women underwent an operative laparoscopy (568/592; 95.9%). The most common indication was infertility (415/592; 70.1%). Diagnostic laparoscopies were mostly indicated for chronic pelvic pain (18/24; 75%). The most common surgical finding was tubo-peritoneal adhesions (412/592; 69.6%). A total of 35 patients (35/592; 5.9%) had at least one complication. The mean duration of hospitalization was 3.4 ±1.8 days. The general uptake of gynaecological laparoscopic surgery is low in our setting. The laparoscopic complication rate of 5.9% is encouraging.